2009
DOI: 10.1111/j.1440-0960.2008.00498.x
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative management and the associated rate of adverse events in dermatological procedures performed by dermatologists in New Zealand

Abstract: Dermatological surgery performed in an outpatient setting is common and generally perceived as safe, but the potential for serious adverse events does exist. Furthermore, there is a current lack of guidelines regarding preoperative and intraoperative monitoring of such patients. This is a retrospective study that involved a written questionnaire sent to current practising New Zealand dermatologists. Aspects investigated include their practice relating to preoperative assessments and intraoperative monitoring d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Two large prospective studies taking place in subtropical Australia found much higher infection rates for simple dermatologic surgery than would normally be expected (8.7% in 972 patients [13], 8.6% in 857 patients [25]). The reasons for this are unclear but we postulate that high ambient temperature and humidity may improve conditions for bacterial colonization.…”
Section: Wound Characteristicsmentioning
confidence: 87%
See 1 more Smart Citation
“…Two large prospective studies taking place in subtropical Australia found much higher infection rates for simple dermatologic surgery than would normally be expected (8.7% in 972 patients [13], 8.6% in 857 patients [25]). The reasons for this are unclear but we postulate that high ambient temperature and humidity may improve conditions for bacterial colonization.…”
Section: Wound Characteristicsmentioning
confidence: 87%
“…In a retrospective review of 8850 elective hand surgery cases, the infection rate was only 0.35% yet 31% received AP [10]. Other recent studies, however, have shown judicious AP use [22,25].…”
Section: Incidence Of Dermatologic Surgical Site Infectionmentioning
confidence: 99%
“…Most infections are attributed to Staphylococcus aureus , which contaminates the wound bed at the time of surgery from the exogenous environment or the patient's skin flora 1,2 . The reported rate of infection in MMS patients is generally lower than these figures, ranging from 0.07% to 3.5% 3–8 …”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Superficial suppuration constitutes the commonest form of infections encountered, systemic infective complications being rare. [2] Postoperative skin infections occur essentially as a result of noncompliance or breach in the standard infection control practices and lead to morbidity, disfigurement and dissatisfaction amongst patients undergoing dermatological surgery. Since many of the procedures are cosmetic procedures, such incidents may also lead to medicolegal consequences.…”
Section: Introductionmentioning
confidence: 99%